2016
DOI: 10.1007/s10803-016-2748-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias to Emotional Faces Varies by IQ and Anxiety in Williams Syndrome

Abstract: Individuals with Williams syndrome (WS) often experience significant anxiety. A promising approach to anxiety intervention has emerged from cognitive studies of attention bias to threat. To investigate the utility of this intervention in WS, this study examined attention bias to happy and angry faces in individuals with WS (N=46). Results showed a significant difference in attention bias patterns as a function of IQ and anxiety. Individuals with higher IQ or higher anxiety showed a significant bias toward angr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 68 publications
(100 reference statements)
4
23
1
1
Order By: Relevance
“…The Spence Children's Anxiety Scale (SCAS; Spence, 1998) The SCAS was administered to parents of WS individuals (Nauta et al, 2004;Spence, 1998). Previous studies have successfully used this scale with children, adolescents, and adults with WS (Dodd, Schniering, & Porter, 2009;McGrath et al, 2016). The SCAS contains 38 items in total, with six subscales, evaluating symptoms on differing domains of anxiety (Nauta et al, 2004).…”
Section: Wj-iii Cogmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spence Children's Anxiety Scale (SCAS; Spence, 1998) The SCAS was administered to parents of WS individuals (Nauta et al, 2004;Spence, 1998). Previous studies have successfully used this scale with children, adolescents, and adults with WS (Dodd, Schniering, & Porter, 2009;McGrath et al, 2016). The SCAS contains 38 items in total, with six subscales, evaluating symptoms on differing domains of anxiety (Nauta et al, 2004).…”
Section: Wj-iii Cogmentioning
confidence: 99%
“…While these results provide evidence that the attention bias for positive social stimuli in WS extends beyond social-perceptual stimuli, certain limitations must be addressed. Although the WS sample recruited for the current study is equivalent in size to other studies in this area (e.g., see Dodd & Porter, 2010;Goldman et al, 2017), it is still a relatively small sample, and did not allow for a comprehensive investigation of withinsyndrome heterogeneity, as seen in McGrath et al (2016). Administering the dot-probe task using the face stimuli developed for this task to a larger number of WS participants would enable us to further investigate how attention to these stimuli may systematically vary as a result of cognitive ability and anxiety symptomatology.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The dot probe compares response times to probes in spatial proximity to threatening or neutral stimuli to quantify a threat-related attentional bias (MacLeod et al 1986). This task has been used to ascertain attentional bias in a variety of child populations, including those with depression (Joormann et al 2007;Neshat-Doost et al 2000;Taghavi et al 1999), post-traumatic stress disorder (Bertó et al 2017;Briggs-Gowan et al 2015;Dalgleish et al 2001), autism spectrum disorder (Hollocks et al 2013;May et al 2015;Moore et al 2012;Zhao et al 2016), Williams syndrome (Dodd and Porter 2010;McGrath et al 2016), asthma (Dudeney et al 2017;Lowther et al 2016), and a range of anxiety disorders (Hunt et al 2007;Salum et al 2013;Sylvester et al 2016;Vasey et al 1995;Waters et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the normality tests and homogeneity of variance tests of RT showed that the data was suitable for analysis of variance. Finally, we used a median split at social anxiety score = 7 to define a LSA (low social anxiety, N = 92, range 0–7) and HSA group ( N = 76, range 8–18, Mcgrath et al, 2016). Then, a Group (LSA and HSA) × Gender (male and female) × Cue Type (happy, disgusted, neutral) ANOVA on the RT was examined for the valid position (to assess hypervigilance) and invalid position (to assess disengagement) separately 1 .…”
Section: Resultsmentioning
confidence: 99%